Production and operations management - Sharma, Abhishek (Toronto Academic Press, 2024)
Production and operations management applies business concepts to create goods and services. Production and Operations Management is an essential guide for anyone seeking to understand the concepts and principles that underpin the efficient management of production processes. The book explores key topics such as inventory management, quality control, and supply chain management, with real-world examples and case studies to illustrate their practical application. With a focus on continuous improvement and the latest technological advancements, the book offers a comprehensive overview of the field of production and operations management.